ANALISIS KINERJA ANGGARAN PENDAPATAN BELANJA DAERAH KABUPATEN MOROWALI PADA PERIODE TAHUN 2011-2015 - Gramini, Media (Fakultas Ekonomi Universitas Tadulako, 2017)
This study aims to determine the performance of local revenue and expenditure budget of Morowali District in the period of 2011-2015. This research is quantitative descriptive. This study uses: (1) analysis performance of the local revenue consisting of variance revenue analysis, regional financial ratio analysis, (2) analysis of local expenditure performance includes: variance analysis of local expenditure, analysis of local expenditure activity, and analysis of local expenditure efficiency. The analysis shows that the performance of Morowali District?s local revenue and expenditure budget is poor due to: (1) variance revenue analysis is rated poorly because it has a negative difference; (2) analysis of local financial ratio shows that: (a) the degree of decentralization is very low, (b) independence ratio is very low with a pattern of instructive relationships, (c) dependence ratio has a high level of dependency and (d) effectiveness ratio is considered ineffective. Meanwhile the analysis of the performance of local expenditure shows: (1) variance expenditure analysis is considered good because it has a positive difference (2) activity ratio of expenditure is rated good while capital expenditure is considered less fit because Morowali District prioritizes its budget for operational expenditure than capital expenditures (3) efficiency analysis of expenditure is rated efficient.